![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 3+2*x=15
2x=15-3
2x=12
x=12:2
x=6
Vậy x=6
b) 24-x=19
x=24-19
x=5
Vậy x=5
c) 29x-13=45
29x=45+13
29x=58
x=58:29
x=2
Vậy x=2
d) 5x-17=38
5x=38+17
5x=55
x=55:5
x=11
Vậy x=11
e) 50-2(x+1)=20
2(x+1)=50-20
2(x+1)=30
x+1+30/2
x+1=15
x=15-1=14
Vậy x=14
f)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\frac{3}{5}-x\right)+\frac{13}{20}=\frac{5}{6}\)
\(\frac{3}{5}-x=\frac{5}{6}-\frac{13}{20}\)
\(\frac{3}{5}-x=\frac{11}{60}\)
\(x=\frac{3}{5}-\frac{11}{60}\)
\(x=\frac{5}{12}\)
\(\left(x-\frac{1}{2}\right)\cdot\frac{5}{3}=\frac{7}{4}-\frac{1}{2}\)
\(\left(x-\frac{1}{2}\right)\cdot\frac{5}{3}=\frac{5}{4}\)
\(x-\frac{1}{2}=\frac{5}{4}:\frac{5}{3}\)
\(x-\frac{1}{2}=\frac{3}{4}\)
\(x=\frac{3}{4}+\frac{1}{2}\)
\(x=\frac{5}{4}\)
( 3/5 - x ) + 13/20 = 5/6
3/5 - x = 5/6 - 13/20
3/5 - x = 89/60
x = 3/5 - 89/60
x = 25/12
( x - 1/2 ) x 5/3 = 7/4 - 1/2
( x - 1/2 ) x 5/3 = 5/4
x - 1/2 = 5/4 : 5/3
x - 1/2 = 35/12
x = 35/12 + 1/2
x = 41/12
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\left(x+3\right)\times5+1=20\Leftrightarrow5x+15=19\)
\(\Leftrightarrow5x=4\Leftrightarrow x=\frac{4}{5}\)
b)sai đề
c)\(2\frac{3}{7}\times x+1\frac{5}{4}=5\frac{3}{42}\)\(\Leftrightarrow\frac{17}{7}\times x+\frac{9}{4}=\frac{71}{14}\) \(\Leftrightarrow\frac{17}{7}\times x+\frac{63}{28}=\frac{142}{28}\)
\(\Leftrightarrow\frac{17}{7}\times x=\frac{79}{28}\Leftrightarrow x=\frac{17}{7}:\frac{79}{28}\) \(\Leftrightarrow x=\frac{17}{7}\times\frac{28}{79}\Leftrightarrow x=\frac{476}{553}=\frac{68}{79}\)
d)\(10\frac{2}{3}-x:\frac{6}{7}=8\frac{1}{3}-6\frac{2}{7}\Leftrightarrow\frac{32}{3}-x:\frac{6}{7}=\frac{25}{3}-\frac{44}{7}\) \(\Leftrightarrow\frac{224}{21}-x:\frac{6}{7}=\frac{75}{21}-\frac{132}{21}\Leftrightarrow-\frac{57}{21}-\frac{224}{21}\)
\(\Leftrightarrow-x:\frac{6}{7}=-\frac{281}{21}\Leftrightarrow-x=-\frac{281}{21}\times\frac{6}{7}\) \(\Leftrightarrow-x=-\frac{1686}{147}\Leftrightarrow x=\frac{562}{49}=11\frac{23}{49}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a,3x-3+6x-12=5
9x-15=5
9x=20
x=20/9
b,3x-6+6x-6=6
9x-12=6
9x=18
x=2
c,4x+4+5x+10=3x+20
9x+14=3x+20
9x-3x=6
6x=6
x=1
a) 3.(x-1) + 6.(x-2) = 5
3.x - 3 + 6.x - 12 = 5
9.x - 15 = 5
9.x = 5 + 15
9.x = 20
x = \(\frac{20}{9}\)
Vậy x = \(\frac{20}{9}\)
b) 3.(x-2) + 6.(x-1) = 6
3.x - 6 + 6.x - 6 = 6
9.x - 12 = 6
9.x = 6 + 12
9.x = 18
x = 18 : 9
x = 2
Vậy x = 2
c) 4.(x+1) + 5.(x+2) = 3.x +20
4.x +4 +5.x +10 = 3.x +20
9.x + 14 = 3.x +20
9.x - 3.x = 20 - 14
6.x = 6
x = 6 : 6
x = 1
Vậy x = 1
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x:\frac{1}{2}+\frac{3}{4}=1\frac{19}{20}\)
\(x:\frac{1}{2}+\frac{3}{4}=\frac{39}{20}\)
\(x:\frac{1}{2}=\frac{39}{20}-\frac{3}{4}\)
\(x:\frac{1}{2}=\frac{39}{20}-\frac{15}{20}\)
\(x:\frac{1}{2}=\frac{24}{20}\)
\(x=\frac{24}{20}.\frac{1}{2}\)
\(x=\frac{3}{5}\)
\(x:\frac{1}{2}+\frac{3}{4}=1\frac{19}{20}\)
\(x:\frac{1}{2}=1\frac{19}{20}-\frac{3}{4}\)
\(x:\frac{1}{2}=\frac{39}{20}-\frac{3}{4}\)
\(x:\frac{1}{2}=\frac{39}{20}-\frac{15}{20}\)
\(x:\frac{1}{2}=\frac{24}{20}\)
\(x=\frac{24}{20}\times\frac{1}{2}\)
\(x=\frac{24}{40}\)
\(x=\frac{3}{5}\)
\(5:\frac{1}{x}+6:\frac{1}{x}-x=\frac{20}{3}\Leftrightarrow\left(5+6\right):\frac{1}{x}-x=\frac{20}{3}\)
\(\Leftrightarrow11:\frac{1}{x}=\frac{20}{3}\Leftrightarrow\frac{1}{x}=11:\frac{20}{3}\)
\(\Leftrightarrow\frac{1}{x}=\frac{33}{20}\Leftrightarrow1.20=x.33\Leftrightarrow20=33x\)
\(\Leftrightarrow x=20:33\Leftrightarrow x=\frac{20}{33}\)